2001
DOI: 10.1002/casp.647
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' sense of community and feeling of unsafety in the urban environment

Abstract: The purpose of this research was to explore adolescents' feeling of unsafety associated with living in the urban context, their perceptions of the quality of social relations (social support from different persons) and sense of community, and the differences according to the size of the city and adolescent gender. A second aim was to analyse the antecedents of feeling of unsafety. In particular, we considered the in¯uence of sense of community, perception of social support and personal involvement in negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 26 publications
(25 reference statements)
7
55
2
3
Order By: Relevance
“…It is also a consistent with the study conducted by (Zani et al, 2001) but, it is varied with the study of Sherritt and Abdullah (2006), which made it, is clear that there are differences in the security function attributed to the direction of the female gender. The listed these differences between the current result and the previous study to the differences in the age of the two samples where the study was conducted, "Sherritt and Abdullah "on both adolescents and adults.…”
Section: Results Of the Study And Its Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is also a consistent with the study conducted by (Zani et al, 2001) but, it is varied with the study of Sherritt and Abdullah (2006), which made it, is clear that there are differences in the security function attributed to the direction of the female gender. The listed these differences between the current result and the previous study to the differences in the age of the two samples where the study was conducted, "Sherritt and Abdullah "on both adolescents and adults.…”
Section: Results Of the Study And Its Discussionsupporting
confidence: 85%
“…The child abuse adversely affects his character, (Hussein, 2008;World Health Org, 2002) studies indicated the prevalence of abuse in Western and Arab societies, while the other studies conducted by (Alghareeb, 2008;Benflis, 2010;Zani et al, 2001) studies conducted the relationship of these to abuse the child's age and gender, attributes of the parents and their characteristics. On the other hand Islamic Sharia and researches by (Shakir, 2005;Contreas & Kerns, 2000) emphasized on the importance of a sense of security and its ability to achieve social and psychological harmonization which is due to this position for the variables of child abuse and psychological security.…”
Section: Problem Of the Studymentioning
confidence: 99%
“…Noise sensitivity was measured with four items (e.g., "I get annoyed when my neighbours are noisy) adopted from Weinstein's (1978) noise sensitivity scale. Sense of security scale was computed of three items (e.g., "I avoid certain areas because I feel insecure there") (Koskela & Pain, 2000, Zani, Cicognani & Albanesi, 2001). The sense of community (SOC) scale included four items.…”
Section: Scales Used As Independent Variablesmentioning
confidence: 99%
“…That is to say, if the members in a community know one another, their sense of security, belonging, trust, and acceptance will be raised through emotional disclosure to one another and close behaviors (McMillan, 1996) [3]. Besides, SOC has positive associations with social cohesion (Wilkinson, 2007) [4], place attachment (Long & Perkins, 2007) [5] and sense of safety (Zani Cicognani, & Albanesi, 2001) [6], if employees are provided with sense of community at workplace, then they are satisfied with their life (Bodla, Afza, Ali, & Naeem, 2015) [7]. It is therefore learned the importance of SOC.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborly Integration: neighborhoods are settings for close ties and frequent interactions among residents. 6. Localism: emphasize involvement in formal neighborhood organizations and the importance of local talkspots, and tend to have diffusely geographic shopping habits.…”
Section: Introductionmentioning
confidence: 99%